DIGITALIZATION AND ECONOMIC GROWTH NEXUS IN THE ASEAN REGION - Putri Kharisma, Vinnandra; Huruta, Andrian (The European Journal of Applied Economics, 2025)
The digitalization of the economy has emerged as a pivotal driver of growth in the ASEAN region. The prevalence of non-cash transactions and e-commerce has increased exponentially in recent years, and these developments have been widely discussed in academic and public discourse. This study examines the impact of e-money and e-commerce on economic growth in 11 ASEAN countries. The data were obtained from the World Bank and the Statista Research Department. The data were analyzed using the System-Generalized Method of Moments (SYS-GMM) model with a dynamic panel data structure. The findings indicate that e-money has no discernible impact on economic growth, whereas e-commerce exerts a positive and statistically significant influence on economic growth. This study highlights that e-commerce is pivotal in facilitating market expansion, enhancing efficiency, and fostering innovation.